Prototype design for the Setkávač mobile application according to the UI/UX design principles - Salnikova, Elina; Šedivá, Zuzana, 1961-; Pour, Jan; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
This work is devoted to designing a user-friendly mobile application ‘Setkávač’ that plans in-person meet-ups. The study's first section examines the fundamental ideas of UI/UX design theory, placing special emphasis on user-centred design. The theoretical framework offers a thorough guidance for design thinking process of this application. Based on the design principles of UX and UI, the prototype of the mobile application is created during the practical stage of this work. The main aim was to design an interactive prototype in Figma program that meets the application’s purposes and user requirements. The whole documentation of the iterative design process, from conception to prototype, offers insights into decision-making and problem-solving techniques. User testing and feedback loops are essential components of development cycle that guarantee that the prototype not only complies with design principles but also reflects end users' expectations and preferences.
Vedoucí práce: Zuzana Šedivá
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: aplikovaná informatika [obor bakal. práce]; bakalářské práce; bachelor's theses